PENGABDIAN KEPADA MASYARAKAT “TERASDigital Peguyangan Kaja” (Transformasi Era Layanan Administrasi Menuju Sistem Digital Desa Peguyangan Kaja Melalui Tanda Tangan Elektronik) - Dana, Gde Wikan Pradnya; Yuniari, Ni Putu Widya; Aryastana, Putu; Kumara, I Made Surya; Bhaskara, Made Adi; Darma, I Gede Wira; Raharja, I Kadek Agus Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Information technology within organizations, companies, and government institutions today plays a very significant role. However, the implementation of information technology in Indonesia still faces challenges in terms of efficiency and effectiveness, particularly in the village governance sector. On July 9, 2024, the Computer Engineering Faculty at Warmadewa University conducted a Community Service Program titled